2021
DOI: 10.1007/s00244-021-00878-4
|View full text |Cite
|
Sign up to set email alerts
|

The Tire Wear Compounds 6PPD-Quinone and 1,3-Diphenylguanidine in an Urban Watershed

Abstract: Prompted by a recent report that 6PPD-quinone (6PPD-q), a by-product of a common tire manufacturing additive that is present in road runoff, is toxic to coho salmon ( Oncorhynchus kisutch ), extracts of water samples collected from an urban river were re-analyzed to determine if this compound was present in stormwater-influenced flows. In addition, extracts were analyzed for 1,3-diphenylguanidine (DPG), which is also used in tire manufacturing. Samples were originally collected in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 25 publications
4
79
1
Order By: Relevance
“…Recently, a quinone derivative of the tire rubber antioxidant N -(1,3-dimethylbutyl)- N ′-phenyl-PPD (6PPD) formed by oxidative transformation, termed 6PPD-quinone, has attracted considerable international attention on PPDs because 6PPD-quinone was identified as the toxicant responsible for acute mortality in the Pacific Northwest coho salmon . Subsequent studies have confirmed the ubiquitous occurrence of 6PPD and 6PPD-quinone in stormwater runoff, surface waters, air particles, and dust. The same pathway may also produce quinones from other PPDs. A more recent study provided new evidence of multiple PPD-derived quinones in environmental media .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a quinone derivative of the tire rubber antioxidant N -(1,3-dimethylbutyl)- N ′-phenyl-PPD (6PPD) formed by oxidative transformation, termed 6PPD-quinone, has attracted considerable international attention on PPDs because 6PPD-quinone was identified as the toxicant responsible for acute mortality in the Pacific Northwest coho salmon . Subsequent studies have confirmed the ubiquitous occurrence of 6PPD and 6PPD-quinone in stormwater runoff, surface waters, air particles, and dust. The same pathway may also produce quinones from other PPDs. A more recent study provided new evidence of multiple PPD-derived quinones in environmental media .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Many are essentially unknown to ecotoxicology despite an apparent prevalence in the environment 3 , 4 and rapid mobilization in stormwater runoff. 5 7 One such CEC is N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine (6PPD), an antiozonant added during the manufacture of tires to help prevent tread degradation. Ozone abiotically converts 6PPD into 6PPD-quinone, as well as other transformation products.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in toxicity between de-icing products were reported, as well as increased toxicity to mayfly larvae at higher temperatures (15 °C) compared to lower temperatures (4–7 °C). Regarding toxicity of tire wear compounds and particles, Johannessen et al ( 2022b ) reported that the maximum levels of 6PPD-quinone in an urban river during storm events exceeded the previously reported LC50 for this compound for Coho salmon (Tian et al 2021 ). However, Navarro et al ( 2022 ) found that microplastics derived from tire rubber were not harmful to sediment-dwelling oligochaetes and insect larvae.…”
Section: Special Issue Articlesmentioning
confidence: 93%
“…Johannessen et al ( 2022a ) demonstrated that hexamethoxymethyl-melamine (HMMM), a compound which is used in the manufacture of tires and is included in the US Environmental Protection Agencies “High Production Volume Challenge Program” is discharged during rain events into urban watersheds in the Greater Toronto Area in Canada. In addition, in another contribution, Johannessen et al ( 2022b ) reported that two other tire wear compounds, 6PPD-quinone and 1,3-diphenylguanidine, are also present at µg/L concentrations in these urban watersheds and these authors predicted that for each hydrological event, the cumulative loads of these compounds entering urban surface water are in kg amounts. This is alarming as Tian et al ( 2021 ) recently reported that 6PPD-quinone is toxic to Coho salmon at concentrations < 1 µg/L.…”
Section: Special Issue Articlesmentioning
confidence: 98%